Fabrication of translucent silicon nitride ceramics with various sintering aids. (10th December 2012) - Yang, W.W.; Inada, M.; Tanaka, Y.; Enomoto, N.; Hojo, J.
Polycrystalline translucent Si3 N4 sintered ceramics are receiving attention owing to their high mechanical strength and chemical stability. Regardless of a long history to sinter Si3 N4, there have been few reports on the fabrication of translucent Si3 N4 ceramics. In this study, the authors used three systems including AlN–MgO, AlN–Y2 O3 and Al2 O3 –Y2 O3 as sintering aids of Si3 N4, and the phase composition and transmittance of sintered samples were compared. The translucent α–sialon formed at a large amount of sintering aids and the translucent β–Si3 N4 formed at a small amount of sintering aids.